An investigation of the groundwater seepage and irrigation return flow of the Middleton area of the Great Fish River - Reynders, Anthony Gerard (Rhodes University, Faculty of Science, Department of Geology, 1984)
From introduction: This study is concerned with the factors responsible for mineralisation of water in the Great Fish River, in particular the irrigation return flow and groundwater seepage components. A small irrigated area in the lower Fish River Basin was chosen for a detailed study of irrigation water input, groundwater and seepage water fluctuati ons, and the affect of soils and rocks on river water mineralisation.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Irrigation -- South Africa -- Great Fish River; Seepage; Groundwater flow -- South Africa -- Great Fish River